Strategi Guru Bimbingan Konseling (BK) Dalam Mengatasi Perilaku Perundungan Pada Sekolah Menengah Atas (SMA) Negeri 3 Kota Bengkulu - Marshela Anggreni; Riyani Ermanti Lubis; Anggi Junia Restika; Dwi Apriani Putri; Fauziah Ulfah Nabilah; Zubaidah (JPT : Jurnal Pendidikan Tematik, 2023)
This research aims to see the forms of bullying behavior in SMA Nelgelri 3 Kolta Bengkulu and also how the Guidance and Counseling (BK) teacher's strategy in overcoming bullying behavior in SMA Nelgelri 3 Kolta Bengkulu. The type of research used is qualitative descriptive, the data collection techniques used are observation techniques, interview techniques and documentation techniques, and the data analysis techniques used are reduction, data presentation and drawing conclusions. The results of this research on bullying behavior among students at SMA Nelgelri 3 Kolta Bengkulu are, the forms of bullying behavior found are pulling the hijab, pulling the head and body, pinching, kicking, lifting the victim and then dropping it, bullying, calling friends by nicknames, calling friends by their shortcomings, giving nicknames to older people, ostracizing, gossiping about friends who do not participate in bullying and posting photos of their friends' shame on social media. Then, the strategies implemented by Counseling and Guidance (BK) teachers in overcoming bullying behavior include providing advice, carrying out supervision, giving warnings, giving punishments, calling parents, and implementing police regulations. They also serve as a forum for students to share their feelings and provide motivational support to victims of bullying.